Effects of Changes in Water Use on Rural Landscape Integrity: Tortum Lake Watershed, Turkey - Angin, Ilker; Karahan, Faris (Journal of Agriculture & Rural Development, 2010)
The effects of changes in water use of Tortum Lake watershed were studied. This study investigates the effects of changes in water use culture, and its reflection on landscape during the last 35 years time period. In the last 35 years of time period, factors which caused the changes in type of water use can be discussed and determined under four subjects, which are; (1) fountains constructed built in Tortum Lake watershed by General Directorate of Rural Services (KHGM) in 1975 (2) facilitating the transportation which increased the urban integration, widespread communication, establishing the drinking and usable water systems, (3) changes in water use of traditional agriculture system and establishment of trout production facilities, and (4) establishment of high plateau roads and spreading the recreational activities. From this study, evident changes in (1) structure of cultural and rural landscape (2) sort of traditional architecture (3) type of household water use, were observed. It was found that water resources are contaminated with household pollutants. Key words: Water use culture; rural landscape; Tortum Lake watershed. DOI: 10.3329/jard.v7i1.4434 J Agric Rural Dev 7(1&2), 139-144, June 2009